Descriptive Analysis of Training Scores in Early Childhood Archery Development Management - Made Diah Karisma Utami; Kadek Yogi Parta Lesmana; I Made Satyawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Early childhood sports coaching management requires a data-driven evaluation system to ensure the sustainability of achievement. This study aims to descriptively analyze the training scores of early age archery athletes as part of the controlling function in sports management. The research method used was quantitative descriptive with a sample of Zen Archery Club athletes. The results of the analysis showed an average score of 234.2 with a standard deviation of 54.2. The findings of the study identified a gap in ability between Recurve athletes (highest score of 315) and Barebow division novice athletes. The percentage of athletes in the "medium" category reached 44%, which indicates the availability of a large stock of potential athletes. The implication of this study is the importance of performance data management as a basis for decision-making for coaches and club managers in developing the next stage of training programs.